Feedback - Time for learner-centric approach - Divya Goel; Sanjay Gupta (Wolters Kluwer Medknow Publications, 2018)
Feedback has been recognized as pillar for effective clinical training. Feedback is a complex, bidirectional process between educator and learner which is influenced by a number of factors. Recently, there is shift from an educator-centric approach to a learner-centric approach that aims to understand how learners seek, receive, and incorporate feedback in their learning process. The objective of this paper is to understand various factors which influence the learner role in learner-centric approach.